Pengaruh Independensi, Kompetensi, Dan Pengalaman Kerja Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi Pada Kantor Akuntan Publik Di Daerah Istimewa Yogyakarta - Zuha Anha Zahrani; Ika Wulandari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The bribery case involving an auditor from the West Java regional office of the Audit Board of Indonesia (BPK), who accepted a bribe to manipulate financial reports in order to obtain an unqualified opinion (WTP) in 2022, has raised concerns about the audit quality of both the audit institution and the government. This study aims to analyze the influence of independence, competence, and work experience on audit quality, with auditor ethics as a moderating variable. The study used a questionnaire as the primary data collection method and SPSS software to conduct quantitative research methods, primarily multiple linear regression and moderation regression tests. The purposive sampling technique used resulted in 65 respondents who met the criteria. The research findings indicate that independence and competence have no effect on audit quality, while work experience has a significant effect on audit quality. It is also concluded that auditor ethics does not moderate the relationship between independence and audit quality, competence and audit quality, nor the relationship between auditor experience and audit quality.